2023
DOI: 10.3389/fendo.2023.1174600
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic expression of thyroid hormone receptor TRβ1 in mammalian retina and anterior ocular tissues

Abstract: The retina is increasingly recognized as a target of thyroid hormone. We previously reported critical functions for thyroid hormone receptor TRβ2, encoded by Thrb, in cones, the photoreceptors that mediate color vision. TRβ1, another Thrb receptor isoform, is widely expressed in other tissues but little studied in the retina. Here, we investigate these N-terminal isoforms by RNA-sequencing analysis and reveal a striking biphasic profile for TRβ1 in mouse and human retina. In contrast to the early TRβ2 peak, TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
2
1
0
Order By: Relevance
“…We hypothesized that the c.283 + 1G>A variant could impact retinal-specific functions mainly involved in cone viability without a major affectation of cone subtype specification that is mediated by TRβ2. In fact, a recent study experimentally demonstrates that TRβ1-knockout mice displayed only minor changes in opsin photopigment expression (Ng et al, 2023), resembling what we observed in our patients. Authors suggest that TRβ1, the predominant TRβ isoform at mature ages, may have a role in the survival of both cone photoreceptors and retinal pigment epithelium cells (Ng et al, 2023), as described in other retinal degeneration models (Ma et al, 2014;Ma et al, 2017;Ma et al, 2022), and now in the IRD patients of our cohort.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We hypothesized that the c.283 + 1G>A variant could impact retinal-specific functions mainly involved in cone viability without a major affectation of cone subtype specification that is mediated by TRβ2. In fact, a recent study experimentally demonstrates that TRβ1-knockout mice displayed only minor changes in opsin photopigment expression (Ng et al, 2023), resembling what we observed in our patients. Authors suggest that TRβ1, the predominant TRβ isoform at mature ages, may have a role in the survival of both cone photoreceptors and retinal pigment epithelium cells (Ng et al, 2023), as described in other retinal degeneration models (Ma et al, 2014;Ma et al, 2017;Ma et al, 2022), and now in the IRD patients of our cohort.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, a recent study experimentally demonstrates that TRβ1-knockout mice displayed only minor changes in opsin photopigment expression (Ng et al, 2023), resembling what we observed in our patients. Authors suggest that TRβ1, the predominant TRβ isoform at mature ages, may have a role in the survival of both cone photoreceptors and retinal pigment epithelium cells (Ng et al, 2023), as described in other retinal degeneration models (Ma et al, 2014;Ma et al, 2017;Ma et al, 2022), and now in the IRD patients of our cohort. Of note, only two putatively pathogenic variants have been identified in the TRβ1 N-terminal domain in patients with congenital hypothyroidism and thyroid dysgenesis (Zhou et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, decreasing the intraretinal levels of THs may represent a retinal strategy, similar to those involving VEGF overexpression or autophagy activation, to reduce oxidative stress and cell damage under hyperglycemic condition. Even though this compelling hypothesis has never been investigated, the presence of TH receptors [10][11][12], of the monocarboxylate transporter 8 [13], of TH responsive cells [14], and of deiodinase enzymes [15,16] in the retina suggests the possibility of a retinal, local regulation of the TH system to reduce retinal stress. For instance, anti-TH treatments in experimental models of congenital retinal diseases have been observed to protect cone photoreceptors from degeneration [17][18][19].…”
Section: Introductionmentioning
confidence: 99%